Applications of Just in Time in Manufacturing Industry. Issue 1 (April 2021) - Agrawal, Manoj Kumar
Abstract: The purpose of assembling organization in current scenario is to provide best quality of output at minimum cost at the correct time. Just in Time (JIT) has been accepted now a day's worldwide as it has many advantages like more throughput time, higher efficiency and best quality. The objective of this paper is to discuss the key issues and all important principles for understanding the framework of JIT implementation. This paper also shows the techniques and pay off of JIT implementation in manufacturing industry. A structured questionnaire survey is used for JIT fabrication methodology. The thoughts introduced within this paper used JIT fabricating in their associations.